2003
DOI: 10.1128/jvi.77.24.13267-13274.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Viral Replication as a Contributor to theDetection of Epstein-Barr Virus in BreastCancer

Abstract: Epstein-Barr virus (EBV)has an accepted association with the epithelial malignancy nasopharyngeal carcinoma and has also been reported in other more controversial carcinoma settings. Evaluation of EBV association with epithelial carcinomas such as breast cancer would benefit from a better understanding of the outcome of EBV infection of these cells. Cell-free preparations of a green fluorescent protein-expressing virus, BX1, were used to infect breast cancer cell lines, which were then examined for EBV gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 53 publications
7
40
2
4
Order By: Relevance
“…In two tumors, BK3 and BK40, BZLF1 expression was observed after different overexposure of the blot. The pattern of expression is similar to what was seen in NPC (7) and in breast tissues (15).…”
Section: Resultssupporting
confidence: 64%
“…In two tumors, BK3 and BK40, BZLF1 expression was observed after different overexposure of the blot. The pattern of expression is similar to what was seen in NPC (7) and in breast tissues (15).…”
Section: Resultssupporting
confidence: 64%
“…However, we observed that our results were compatible with the literature ones; it is possible that some prior findings may have been exaggerated by the phenomenon of lytic viral replication as identified by Huang et al [25]. The identification of EBV in this current study, using PCR standard, in situ PCR and immunohistochemistry, is consistent with the findings of others authors.…”
Section: Epstein-barr Virus (Ebv) Is a Human Herpesvirus Type 4 (Hhv-supporting
confidence: 83%
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, four articles could be additionally identified (36,39,41,43), which should have been included in the SR by Huo et al (17) who performed an electronic search for articles published up to September 2010. Furthermore, an additional nine case-control studies published (45-53) thereafter were additionally acquired.…”
Section: Discussionmentioning
confidence: 99%